A dispatching strategy for electric vehicle aggregator combined price and incentive demand response. Issue 4 (31st August 2021) - Hou, Hui; Wang, Yifan; Xie, Changjun; Xiong, Binyu; Zhang, Qingyong; Huang, Liang
Abstract: Electric vehicles (EVs) have excellent demand response potential, but a single type of demand response is difficult to fully utilise the dispatching potential of EVs. To improve the utilisation of the demand response potential of EVs, this study proposes two kinds of dispatching strategies for electric vehicle aggregator (EVA) combined price‐based and incentive‐based demand response: long‐term contract strategy and short‐term contract strategy. The difference of the two strategies depends on the length of time for EV users to sign incentive agreements with EVA. The long‐term contract strategy assumes that some EV users sign a long‐term incentive agreement with the EVA. The short‐term contract strategy takes an EV charging process as the dispatching cycle. The objective of maximising revenues and minimising load fluctuation of EVA is optimised in two strategies. An improved multi‐objective particle swarm optimisation algorithm that combines region selection strategy and grouping strategy is used to solve the problem. The simulation results show that the two dispatching strategies can improve the comprehensive benefits of EVA as well as EV users. The two dispatching strategies can effectively improve the utilisation of dispatching potential of EVs.